Myths and Methodologies: Reducing scientific design ambiguity in studies comparing sexes and/or menstrual cycle phases. Issue 10 (15th August 2018) - Sims, Stacy T.; Heather, Alison K.
Abstract : New Findings: What is the topic of this review? We review methodological considerations for the inclusion of women in sex and menstrual cycle phase comparison studies. What advances does it highlight? Improving the methodological design for studies exploring sex differences, menstrual cycle phase differences and/or endogenous versus exogenous female sex hormones will help to close the gap in our understanding of the effects of endogenous and exogenous hormones on exercise science and sports medicine outcomes. Abstract: In recent years, the increase in scientific literature exploring sex differences has been beneficial to both clinicians and allied health science professionals, although female athletes are still significantly under‐represented in sport and exercise science research. Women have faced exclusion throughout history though the complexities of sociocultural marginalization and biomedical disinterest in women's health. These complexities have contributed to challenges of studying women and examining sex differences. One underlying complexity to methodological design may be hormonal perturbations of the menstrual cycle. The biphasic responses of oestrogen and progesterone across the menstrual cycle significantly influence physiological responses, which contribute to exercise capacity and adaptation in women. Moreover, oral contraceptives add complexity through the introduction of varying concentrations of circulating exogenous oestrogen and progesterone, which may moderate physiological adaptations to exercise in a different manner to endogenous ovarian hormones. Thus, applied sport and exercise science research focusing on women remains limited, in part, by poor methodological design that does not define reproductive status. By highlighting specific differences between phases with regard to hormone perturbations and the systems that are affected, methodological inconsistencies can be reduced, thereby improving scientific design that will enable focused research on female athletes in sports science and evaluation of sex differences in responses to exercise. The aims of this review are to highlight the differences between endogenous and exogenous hormone profiles across a standard 28–32 day menstrual cycle, with the goal to improve methodological design for studies exploring sex differences, menstrual cycle phase differences and/or endogenous versus exogenous female sex hormones. Abstract :